Nonsurgical management of an extensive endodontic lesion in an orthodontic patient by calcium-enriched mixture apical plug - Asgary, Saeed (Medknow Publications & Media Pvt Ltd, 2014)
Periapical lesion is a general term used to describe the periapical inflammatory process that occurs in response to the invasion of micro-organisms in the root canal system as well as inflamed vital pulp. This phenomenon necessitates endodontic intervention and if the necrosis has occurred prior to tooth maturation, wide patency of the apical foramen requires some treatment modalities such as apexification or apical plug. Orthodontic treatment, on the other hand, is cautiously done for previously traumatized teeth due to increased risk for necrosis of the compromised tooth. This article tends to review the successful treatment process with calcium-enriched mixture (CEM) cement apical plug for an immature previously traumatized incisor tooth with an extensive periapical lesion, which was under orthodontic treatment as well.